An efficient method for the dynamic analysis of planetary roller screw mechanism. (August 2020) - Fu, Xiaojun; Liu, Geng; Ma, Shangjun; Tong, Ruiting; Li, Xin
Highlights: An efficient method for the dynamic analysis of the PRSM is proposed. CPU time of the proposed model is only about 4% of that of the previous model. Internal forces of the PRSM are included in the equations of generalized forces. Effect of structural parameters on the dynamic behavior of the PRSM is analyzed. Abstract: A dynamic model of the planetary roller screw mechanism (PRSM) is proposed by combining Lagrange's method and Newton's second law, which can be used to determine the motion and internal forces of the PRSM efficiently. The generalized forces corresponding to the rotational angles of the screw and carrier are given with considering the forces acting on the screw, roller, nut, carrier and ring gear. Using Lagrange's method, the rotational acceleration of the carrier and the driven torque of the screw are obtained. The motion equations which include the internal forces are then derived by using Newton's second law. Furthermore, a promising algorithm of solving the derived equations is illustrated. The experiment is carried out to testify the validity of the proposed model. The simulation results obtained from the proposed model and those from the previous model are also compared. Although the simulation results are nearly the same, the CPU time of the proposed model is only about 4% of that of the previous model. Finally, the effect of structural parameters on the dynamic behaviors of the PRSM is discussed.